PENGEMBANGAN UMKM LAUNDRY SEPATU MELALUI DIGITALISASI TRANSAKSI - Fitrah Rumaisa; Yan Puspitarani; Sriyani Violina; Feri Sulianta (JURNAL ILMIAH EDUNOMIKA, 2024)
Computers have become an inseparable part of society's activities, especially in the need to support business processes, so the need for computerized systems has a very essential role in carrying out business processes. However, quite a few still use manual systems in carrying out business activities. As a result, obstacles arise as the business continues to grow due to increasingly large and complex needs. One of them is also experienced in the shoe laundry business which requires complex handling considering the large number of services as the number of consumers increases. In order to meet the needs of existing business processes, a computer-based transactional system is needed to support existing business processes, so that business efficiency and effectiveness can be realized. Further training is also needed due to the transition from manual systems to computer-based systems so that workers can adapt to using computerized systems. precisely on target.